Softening and Shape Morphing of Stiff Tough Hydrogels by Localized Unlocking of the Trivalent Ionically Cross‐Linked Centers. Issue 12 (11th May 2018) - Wang, Jiahui; Li, Tianzhen; Chen, Fan; Zhou, Dan; Li, Baijia; Zhou, Xiaohu; Gan, Tiansheng; Handschuh‐Wang, Stephan; Zhou, Xuechang
Abstract: The mechanical properties (e.g., stiffness, stretchability) of prefabricated hydrogels are of pivotal importance for diverse applications in tissue engineering, soft robotics, and medicine. This study reports a feasible method to fabricate ultrasoft and highly stretchable structures from stiff and tough hydrogels of low stretchability and the application of these switchable hydrogels in programmable shape‐morphing systems. Stiff and tough hydrogel structures are first fabricated by the mechanical strengthening of Ca 2+ ‐alginate/polyacrylamide tough hydrogels by addition of Fe 3+ ions, which introduces Fe 3+ ionically cross‐linked centers into the Ca 2+ divalent cross‐linked hydrogel, forming an additional and much less flexible trivalent ionically cross‐linked network. The resulting stiff and tough hydrogels are exposed to an L‐ascorbic acid (vitamin C, VC) solution to rapidly reduce Fe 3+ to Fe 2+ . As a result, flexible divalent ionically cross‐linked networks are formed, leading to swift softening of the stiff and tough hydrogels. Moreover, localized stiffness variation of the tough hydrogels can be realized by precise patterning of the VC solution. To validate this concept, sequential steps of VC patterning are carried out for local tuning of the stiffness of the hydrogels. With this strategy, localized softening, unfolding, and sequential folding of the tough hydrogels into complex 3D structures is demonstrated. Abstract : Stiffened tough hydrogels are softened by chemically unlocking the ionically cross‐linked ferric networks via in situ reduction by exposure to L‐ascorbic acid (VC). Complex 3D structures can be programmably folded, unfolded, and refolded by localized encoding of softened structures when combing with the surface patterning of VC.